Structure sensitivity of selective catalytic reduction of NO with propylene over Cu-doped Ti0.5Zr0.5O2-d catalysts - Liu, J.; Zhao, Q.; Li, Xin Yong; Chen, J.; Zhang, D. (Elsevier, 2015)
© 2014 Elsevier B.V. The structure sensitivity of selective catalytic reduction (SCR) of NO with propylene over Cu-doped Ti0.5Zr0.5O2-d catalysts was investigated systematically in a series of characterizations and in situ DRIFT spectroscopy. A Cu-doped Ti0.5Zr0.5O2-d catalyst with a hierarchical structure was fabricated successfully using a hydrothermal method (Hy-Sample), and shown to exhibit excellent SCR performance with high reaction rate and turnover frequency (TOF). The physico-chemical properties, mass transfer, and SCR activity of the catalyst depended on the preparation method. Another sample of Cu-doped Ti0.5Zr0.5O2-d catalyst prepared using a co-precipitation method (Co-Sample) exhibited a disordered, irregular morphology, whose SCR activity, as determined in a fixed bed reactor, was significantly lower than that of Hy-Sample. In comparison, Hy-Sample possessed an enhanced redox property, and its highly ordered morphology greatly promoted the generation of active sites, including the fine-dispersed CuO species and surface adsorbed oxygen. Consequently, NO and C3H6 were readily adsorbed and activated over Hy-Sample and induced the formation of important intermediates with high reactivity, such as isocyanate (-NCO) and cyanide (-CN) species. However, the activation capacity of Co-Sample toward reactants was very weak, and the sequential deficiency of N-containing organics could be the primary reason for the poor SCR activity of Co-Sample.